1974
DOI: 10.1007/bf00011413
|View full text |Cite
|
Sign up to set email alerts
|

Volatile selenium in higher plants the production of dimethyl selenide in cabbage leaves by enzymatic cleavage of Se-methyl selenomethionine selenonium salt

Abstract: The volatile selenium compound produced by cabbage (Brassica oleracea vat. Capitata) when cultured on media containing either selenite or selenate is dimethyl selenide, (CH3)2 Se. The dimetbyl selenide arises from enzymatic cleavage of a Se-methyl selenomethionine selenonium compound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 27 publications
1
33
1
Order By: Relevance
“…Arabidopsis and Indian mustard, which are non-halophytes, SeMM is more likely to be the precursor of DMSe rather than DMSeP. Lewis et al (1974) demonstrated that Se-methyl Se-Met was the source of DMSe production in cabbage (Brassica oleracea) leaves. This idea is supported by the fact that DMSeP was not detected in Se-Met-supplied Indian mustard plants, although they were capable of taking up, assimilating, and volatilizing Se at high rates when supplied with DMSeP (de Souza et al, 2000).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Arabidopsis and Indian mustard, which are non-halophytes, SeMM is more likely to be the precursor of DMSe rather than DMSeP. Lewis et al (1974) demonstrated that Se-methyl Se-Met was the source of DMSe production in cabbage (Brassica oleracea) leaves. This idea is supported by the fact that DMSeP was not detected in Se-Met-supplied Indian mustard plants, although they were capable of taking up, assimilating, and volatilizing Se at high rates when supplied with DMSeP (de Souza et al, 2000).…”
mentioning
confidence: 98%
“…The major volatile Se form produced by plants and microbes is dimethylselenide (DMSe; Lewis et al, 1974). DMSe is 600 to 700 times less toxic than selenate or selenite, two Se species that are commonly present in polluted areas (McConnell and Portman, 1952;Ganther et al, 1966;Wilber, 1980).…”
mentioning
confidence: 99%
“…A large proportion of the Se removed by the wetland was accumulated in plant tissues and sediments, and it was estimated that 10% to 30% of the removed Se was volatilized. Se volatilization is the process by which inorganic Se is converted to volatile forms (Lewis et al, 1966;Evans et al, 1968;Lewis, 1971;Frankenberger and Karlson, 1994;Terry and Zayed, 1994). Dimethylselenide, the predominant form of volatile Se, is 500 to 700 times less toxic than inorganic forms of Se (McConnell and Portman, 1952;Ganther et al, 1966;Wilber, 1980).…”
mentioning
confidence: 99%
“…Dimethyl selenide is the principle compound released by microbial and plant respiration (Lewis et al, 1966(Lewis et al, , 1974Francis et al, 1974). Volatile Se was first collected from accumulator and nonaccumulator plants by Lewis et al (1966Lewis et al ( , 1974, and the volatile Se respired by the accumulator A. racemosus was identified as DMSe (Lewis et al, 1974).…”
Section: Selenium Volatilitymentioning
confidence: 99%